Analisis Pengaruh Kepuasan Kerja terhadap Turnover Intention Karyawan di PT Gemilang Succes Bersatu - Yohanita Indraningrum; Mei Retno Adiwati (MES Management Journal, 2025)
This study aims to analyze the effect of job satisfaction on employee turnover intention at PT Gemilang Succes Bersatu. The research method used is quantitative with a survey approach, data collected through a Likert scale-based questionnaire. Data were analyzed using simple linear regression to determine the relationship between job satisfaction variables and turnover intention.